A STUDY OF PHONOLOGICAL ERRORS IN STUDENTS’ ENGLISH SPEECH PRODUCTION - Medi, Divo Zidane Akbar Nugraha; Hasibuan, Hapni Nurliana H.D.; Jismulatif; Miftahul Jannah; Teresia Nataline Sitorus (Magister Scientiae, 2026)
Phonology is significant in facilitating communication, especially for university students who are learning English as a foreign language. The purpose of the study is to determine the types and causes of pronunciation errors made by students of FKIP Universitas Riau. A descriptive qualitative study was conducted by selecting sixteen students from various study programs. Pronunciation tests, recordings, and interviews were used as data collection methods, and data were analyzed using the International Phonetic Alphabet. The study identified eight types of phonological errors, characterized by vowel substitution, silent letter pronunciation, diphthong simplification, consonant substitution, cluster reduction, voicing, epenthesis, and spelling pronunciation. These errors are caused by the Indonesian phonological system, a lack of pronunciation practice, and students’ need to speak English. These findings show that pronunciation errors are common among university students and need more attention in English pronunciation classes.